2014
DOI: 10.1103/physrevlett.112.180603
|View full text |Cite
|
Sign up to set email alerts
|

Work Output and Efficiency at Maximum Power of Linear Irreversible Heat Engines Operating with a Finite-Sized Heat Source

Abstract: We formulate the work output and efficiency for linear irreversible heat engines working between a finite-sized hot heat source and an infinite-sized cold heat reservoir until the total system reaches the final thermal equilibrium state with a uniform temperature. We prove that when the heat engines operate at the maximum power under the tight-coupling condition without heat leakage the work output is just half of the exergy, which is known as the maximum available work extracted from a heat source. As a conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 34 publications
(55 reference statements)
7
94
0
Order By: Relevance
“…For thermochemical engines it was shown that the form of the EMP [25] is controlled by the symmetries of the underlying dynamics (see also [26] for a similar study, but with finite-sized reservoirs). This result was further precised [27] and recently a similar argumentation was successfully used for general thermodynamic devices [28].…”
Section: Introductionmentioning
confidence: 99%
“…For thermochemical engines it was shown that the form of the EMP [25] is controlled by the symmetries of the underlying dynamics (see also [26] for a similar study, but with finite-sized reservoirs). This result was further precised [27] and recently a similar argumentation was successfully used for general thermodynamic devices [28].…”
Section: Introductionmentioning
confidence: 99%
“…The seminal results of Carnot apply to the case of infinite reservoirs. However, in recent years, the study of the role of finite reservoirs has also caught attention [1][2][3][4][5][6][7]. This is motivated by practical considerations such as a limited supply of fuel (a finite heat source), or the working medium being in contact with a small environment (sink) which may be the case in small-scale devices, or even relevant for the design of modern cities.…”
Section: Introductionmentioning
confidence: 99%
“…Heat engines that attain their maximal power and maximal efficiency (which is either the Carnot efficiency or a lower value) at different working conditions are here defined as heat engines with a power-efficiency trade-off. The power-efficiency trade-off is the subject of many recent studies [3,[6][7][8][9][10][11].Less is known about the efficiency and power of cyclic heat engines, but a lot of research effort has been devoted to understanding them in recent years [12][13][14][15][16][17][18][19]. The operation of a cyclic engine is characterized by a protocol that describes the time dependence of key variables along the cycle -e.g.…”
mentioning
confidence: 99%
“…Heat engines that attain their maximal power and maximal efficiency (which is either the Carnot efficiency or a lower value) at different working conditions are here defined as heat engines with a power-efficiency trade-off. The power-efficiency trade-off is the subject of many recent studies [3,[6][7][8][9][10][11].…”
mentioning
confidence: 99%